Effect of sucrose on cryopreservation of pig spermatogonial stem cells - Chuan-ying PAN; Shuai YU; Peng-fei ZHANG; Bo WANG; Zhen-dong ZHU; Ying-ying LIU; Wen-xian ZENG (Journal of Integrative Agriculture)
Sucrose is known to play an important role in the cryopreservation of sperm and female gonads; however, its effect on the cryopreservation of pig spermatogonial stem cells (pSSCs) has not been tested. The aim of this work was to study the effect of sucrose during pSSC cryopreservation and to find the most effective concentration in freezing medium. pSSCs were cryopreserved with freezing media containing different concentrations of sucrose (70, 140, 210, and 280 mmol L−1) and a control group without sucrose. The survival rates, plasma membrane integrity, and mitochondrial membrane potential of thawed cells were detected by trypan blue (TB) staining, SYBR-14/propidium iodide (PI) dual staining, and JC-1 staining, respectively. All the staining results showed an obvious increase in cell survival in the sucrose-treated groups as compared to that in the control group, with the exception of 280 mmol L−1 sucrose. Moreover, the 210 mmol L−1 sucrose group yielded the highest survival rate among all the groups (P<0.05). The results of SYBR-14/PI dual staining and JC-1 staining were consistent with those of TB staining as above described. Quantitative real-time PCR (qRT-PCR) indicated that the mRNA levels of three apoptosis-promoting genes (BAX, APAF1 and CASPASE9) were significantly higher in thawed cells than in cells before freezing (P<0.05). Moreover, the mRNA level of one anti-apoptotic gene (XIAP) was significantly lower in thawed cells than in cells before freezing (P<0.05). When comparing the mRNA expression of apoptosis-related genes in thawed cells, the mRNA level of the anti-apoptotic genes in the control group was significantly lower than that in the sucrose-treated groups (P<0.05). Western blot analyses showed that the expression levels of cleaved CASPASE9, CASPASE3 and PARP-1 in the sucrose-treated groups were lower than those in the control group and were the lowest in the 210 mmol L−1 sucrose group. Both qRT-PCR and Western blot analyses suggested that sucrose inhibited cell apoptosis during freezing and thawing. Briefly, sucrose promoted pSSCs survival after freezing and thawing, especially at a concentration of 210 mmol L−1, which possibly assisted pSSC dehydration and inhibited cell apoptosis. These findings hold great promise for further studies of the regulatory mechanism of proliferation and differentiation of pSSCs.